Ergogenic effect of hyperoxic recovery in elite swimmers performing high-intensity intervals - Sperlich, B.; Zinner, C.; Krueger, M.; Wegrzyk, J.; Mester, J.; Holmberg, H. C. (Scandinavian Journal of Medicine & Science in Sports, 2011)
This investigation tested the hypothesis that breathing oxygen-enriched air (FiO2=1.00) during recovery enhances peak (Ppeak) and mean power (Pmean) output during repeated high-intensity exercise. Twelve elite male swimmers (21 ± 3 years, 192.1 ± 5.9 cm, 79.1 ± 8.2 kg) inhaled either hyperoxic (HOX) or normoxic (NOX) air during 6-min recovery periods between five repetitions of high-intensity bench swimming, each involving 40 maximal armstrokes. Oxygen partial pressure (pO2) and saturation (SO2), [H+], pH, base excess and blood lactate concentration were measured before and after all intervals. The production of the reactive oxygen species (ROS) hydrogen peroxide was measured before, directly after and 15 min after the test. Ppeak and Pmean with HOX recovery were significantly higher than with NOX throughout the third, fourth and fifth intervals (P<0.001-0.04). With HOX, electromyography activity was lower during the third, fourth and fifth intervals than during the first (P=0.05-0.001), with no such changes in NOX (P=0.99). There were no differences in blood lactate, pH, [H+] or base excess and ROS production at any time point with either HOX or NOX recovery. These findings demonstrate that the Ppeak and Pmean of elite swimmers performing high-intensity intervals can be improved by exposure to oxygen-enriched air during recovery.